TRANSPORT SECTOR AND ITS ROLE IN THE IMPORT SUBSTITUTION OF AGRICULTURAL PRODUCTS: FORESIGHT - V. Persianov (Publishing House of the State University of Management, 2016)
The article gives a description of the practical experience of soviet railway transport in part-time gardening and farming. It also proposes a project of factory-farm integration to ensure the economic security of our country.